REPEAT-PASS INTERFEROMETRIC AND BACKSCATTER ANALYSIS OF X-BAND PAZ SATELLITE – FIRST RESULTS - S. Abdikan; C. Bayik; M. Ustuner; F. Balik Sanli (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2020)
In this paper we present the initial results of PAZ Synthetic Aperture Radar (SAR) imagery for the first time. In the study, the potential of repeat-pass high resolution PAZ images were investigated. To this aim, both linear backscatter and interferometric results were presented. We used multi-temporal X-band (3.1 cm wavelength) new generation single look complex (SLC) data from Spanish PAZ in single polarization data. PAZ is based on TerraSAR-X/TanDEM-X platform to establish a constellation with them to shorten the revisit time and increase data acquisition capacity. We applied two analysis on PAZ data to assess the performance of the satellite images. For the analysis a semi-arid and almost flat region of Central Anatolia was selected. The images are acquired in both ascending and descending orbits. Each pair has 33 days of temporal baselines. Firstly, backscatter analysis was conducted over the region for different land cover classes. Secondly interferometric analysis was applied to determine phase difference and coherence features. As the region has sand dunes, bareland and uncultivated agricultural fields the coherence analysis showed high values, while cultivated fields showed variations of coherence due to different growth of vegetation. Since the region is prone to sinkhole formation the high-resolution PAZ indicated its advantage as determining a sinkhole that has a circle shape. The displacement of ground surface is determined in line of sight direction.